PENGARUH BRAND EXPERIENCE TERHADAP BRAND LOYALTY YANG DIMEDIASI OLEH BRAND LOVE PADA GEN Z DI KABUPATEN KLATEN MEMILIH MERK SNEAKERS LOKAL - Hadi, Abdulhadi; Wisnu Barata, Dody Muhamad; Hardoko, Hardoko; Yusti, Yusti (Sekolah Tinggi Ilmu Ekonomi SBI, 2024)
Abstract This study aims to analyze the influence of brand experience on brand loyalty, with brand love as a mediating variable among Gen Z in Klaten Regency in choosing local sneaker brands. The research employs a quantitative approach with a survey method. Data were collected from 107 respondents selected through purposive sampling and analyzed using path analysis and Sobel test to examine mediation. The findings indicate that brand experience has a positive and significant effect on brand loyalty (β = 0.257; p = 0.011) and brand love (β = 0.604; p = 0.000). Additionally, brand love significantly influences brand loyalty (β = 0.609; p = 0.000). The Sobel test confirms that brand love significantly mediates the relationship between brand experience and brand loyalty (t = 3.711; p = 0.000). These findings suggest that a positive brand experience directly enhances consumer loyalty and indirectly strengthens it through brand love. Practical implications highlight the need for local sneaker brands to focus on improving brand experience and fostering emotional connections with consumers to build stronger loyalty Keywords: Brand Experience, Brand Loyalty, Brand Love, Local Sneakers, Gen Z